Impact of Teaching Academic Text Cohesive Devices on ESL Undergraduates’ Listening Comprehension - Mohammad Nasim, Tahsildar; Zailin Shah, Yusoff (Macrothink Institute, 2014)
This paper reports on a study investigating the effects of teaching academic text cohesive devices on ESL students’ listening comprehension. The main objective of the study was to find out if through teaching cohesive devices would enhance students’ prior knowledge and subsequently result in increased listening comprehension. Based on a pre-test post-test research design, 40 students enrolled in English for Academic Purposes course at a university in Malaysia were engaged as participants. A listening comprehension test was conducted prior to and post-intervention. The intervention consisted of lessons on academic text cohesive devices. The data were then analysed and reported using descriptive statistics and paired samples t-test. From the findings, it was clear that there was an increase in the minimum and maximum scores as well as in the mean scores between the pre- and post-test scores. More importantly, there was evidently a significant improvement in the participants’ post-test listening comprehension scores as compared to the pre-test scores. In sum, the teaching of academic text cohesive devices does have a significant impact on ESL learners’ listening comprehension. Hence, two recommendations for the teaching of listening to ESL learners are: one; to recognize the place of prior knowledge in enhancing comprehension and two; to facilitate listening comprehension through appropriate pre-, while- and post-listening activities.